Study on global navigation satellite system (GNSS) ground infrastructures in Malaysia - Subari, Mustafa Din (2004)
There are currently two Global Navigation Satellite System (GNSS) core systems namely Global Positioning System (GPS) and GLObal NAvigation Satellite System (GLONASS). The GALILEO is expected to be up by 2008. The dependency on these space-based technology for navigation, positioning and timing is on the increase globally, and it is expected to be ‘the’ vital system worldwide in future. The present service of GPS has encouraged the acceptance and integration of the technology into peaceful civil, commercial, and scientific applications worldwide. Presently, users in most developing countries are accessing to the system on their own through services provided by the core system service provider, or augmentation systems provided by commercial companies. Issues such as integrity, accuracy, availability, and continuity are not adequately addressed. Lacking of these requirements may lead to occurrence of catastrophes such as ship collisions, landing failures, and etc. To ensure GNSS services to be more reliable and efficient, many developed nations such even the United States of America (USA), Europe and Japan are working on in establishing appropriate augmentation infrastructures for their local users. This paper reviews the current GNSS infrastructures that are available in marine, land and aviation sectors locally with global development in mind.